Gamma knife radiosurgery for jugular foramen schwannomas - (:unkn) unknown (SPRINGER, 2012)
Jugular foramen schwannomas are very rare tumors. Advances in skull base surgery have led to more aggressive resection of these tumors, but surgery may associate with development of new neurological deficits. In this report, we analyze the long-term results for 17 patients with newly diagnosed or residual/recurrent jugular foramen schwannoma who underwent gamma-knife treatment. During a mean 64 months of follow-up, magnetic resonance imaging revealed reduced tumor size in 13 cases and no size change in four cases. The tumor growth control rate was 100% and only one patient had transient hoarseness. For patients who have small- to moderate-sized jugular foramen schwannomas, gamma-knife radiosurgery is associated with good tumor control and carries minimal risk of adverse radiation effects.
Keywords: Gamma knife; Jugular foramen; Radiosurgery; Schwannoma; STEREOTACTIC RADIOSURGERY; NONACOUSTIC SCHWANNOMAS; MANAGEMENT; PRESERVATION